Analysis of Post-Internship Student Interest in Working in Islamic Banks (Study on IAIN Bone Students) - Winda; Abd.Rasyid R. R.; Shadriyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
This research aims to analyze students' interest in working at Islamic banks after completing internships, focusing on students at IAIN Bone. Students' career choices following internships are influenced by various factors, both internal and external. These factors include the alignment between students' personal values and Islamic principles, positive internship experiences, and career prospects offered by Islamic banks. The research employs a qualitative approach with in-depth interviews and observations to explore students' perceptions and motivations. The findings indicate that positive internship experiences, understanding of Islamic values, and alignment between students' personal goals and Islamic banking values play important roles in increasing their interest in working in this sector. Additionally, external factors such as job stability and career opportunities in Islamic banks serve as key drivers. The research suggests that Islamic banks and universities should strengthen internship programs and enhance students' understanding of the Islamic banking sector to attract more qualified talent to work in this field.